Effect of quercetin on altered vascular reactivity in aortas isolated from streptozotocin-induced diabetic rats - Ajay, Machha; Achike, Francis I.; Mustafa, Ali Mohd; Mustafa, Mohd Rais (Elsevier, 2005)
The present work examined ex vivo the acute effect of quercetin on diabetic rat aortic ring reactivity in response to endotheliumdependent (acetylcholine, ACh) and endothelium-independent (sodium nitroprusside, SNP) relaxants, and to the a1-adrenergic agonist phenylephrine (PE). Responses were compared to those of aortic rings from age- and sex-matched euglycemic rats. Compared to euglycemic rat aortic rings, diabetic rings showed less relaxation in response to ACh and SNP, and greater contraction in response to PE. Pretreatment with quercetin (10 mM, 20 min) increased ACh-induced relaxation and decreased PE-induced contraction in diabetic, but did not affect euglycemic rat aortic ring responses. Following pretreatment with the nitric oxide synthase inhibitor Nv-nitro-L-arginine methyl ester (L-NAME, 10 mM), quercetin reduced PE-induced contractions in both aortic ring types, although L-NAME attenuated the reduction in the diabetic rings. Quercetin did not alter SNP vasodilatory effects in either ring type compared to their respective controls. These ﬁndings indicate that quercetin acutely improved vascular responsiveness in blood vessels from diabetic rats, and that these effects were mediated, at least in part, by enhanced endothelial nitric oxide bioavailability. These effects of quercetin suggest the possible beneﬁcial effects of quercetin in vivo in experimental diabetes and possibly in other cardiovascular diseases.